Biohydrogen Machinery: Recent Insights, Genetic Fabrication, and Future Prospects - Madavi, Tanushree Baldeo; Chauhan, Sushma; Jha, Meenakshi; Choi, Kwon Young; Pamidimarri, Sudheer D.V.N. (Chemical Engineering and Technology, 2023)
The increase in global carbon footprints forced mankind to look for alternative carbon-free fuels. Biohydrogen is an ideal fuel, free of carbon footprint, which has the potential to replace fossil fuels. Its high energy content per gram has a great commercial value. Bacteria, cyanobacteria, and algae are developed with various cellular machineries for hydrogen production. Detailed information on these hydrogen-producing cellular machineries, their mechanism of catalysis, and modern genetic engineering and fabrication studies for the enhancement of hydrogen production are reviewed and discussed.
Keywords: Bio-hydrogen; Biophotolysis; Carbon-free; Cellular machinery; Cyanobacterium; Dark fermentation; Energy content; Future prospects; Biohydrogen; Biophotolysis; Dark fermentation; Genetic engineering; Hydrogen production